(untitled) (Communications in Computational Physics, 2018)
The extension of diamond scheme for diffusion equation to three dimensions is presented. The discrete normal flux is constructed by a linear combination of the directional flux along the line connecting cell-centers and the tangent flux along the cell-faces. In addition, it treats material discontinuities by a new iterative method. The stability and first-order convergence of the method are proved on distorted meshes. The numerical results illustrate that the method appears to be approximate second-order accuracy for solution.